Open Tender for the Right to Conclude an Agreement on Conductinga Mandatory Audit of Financial Statements - Y. B. Lavrov (Сибирское юридическое обозрение, 2018)
The Author highlights some problems of the correlation of the legislation on auditing activity and the law on the contract system in the sphere of procurement with regard to holding an open tender for compulsory audit by a number of legal entities. There are violations of the rules of legal technology in the construction of terminological apparatus. The article deals with the issues concerning the correlation of private and public principles in the law on the contract system in the sphere of procurement of goods, works and services for provision of public needs. A conclusion is drawn on the complexity of the legal regulation of state and municipal purchases. The problem connected with the scope of the rules of the law on the contract system in the procurement sphere, which should be used in compulsory audit competitions, was investigated. The need to improve legislation is summarized.